Towards the harmonization of global environmental flow estimates: comparing the Global Environmental Flow Information System (GEFIS) with country data - Eriyagama, Nishadi; Messager, M. L.; Dickens, Chris; Tharme, R.; Stassen, R. (International Water Management Institute, 2024)
The source of data used to estimate the e-flow requirement in Sustainable Development Goal (SDG) Indicator 6.4.2 (level of water stress: freshwater withdrawal as a proportion of available freshwater resources) is the Global Environmental Flow Information System (GEFIS), an online tool produced and managed by the International Water Management Institute (IWMI). In addition to the GEFIS estimate, the Food and Agriculture Organization of the United Nations (FAO), as the custodians of the SDG indicator, encourages countries to put forward their locally determined e-flow estimates, especially if it differs from the GEFIS estimate. To date, however, only a few countries have taken up this opportunity. The aim of this report is to compare e-flows estimated by GEFIS with independent e-flow assessments performed at the local level to gauge the level of agreement between the two sets of estimates. We compared e-flow estimates from GEFIS to local e-flow estimates at 533 river sites.